Analysis of the Indonesian Government's Efforts to Improve the World Ranking in SGIE (State of the Global Islamic Economy) in 2023 by Strengthening the Halal Value Chain Ecosystem and Digital Ecosystem - Hasbullah, Baiq Liza Hayani; Elbadriati, Baiq; Masykuroh, Ely (Electronic Journal of Education, Social Economics and Technology, 2025)
This research aims to determine the efforts made by the Indonesian government to advance Indonesia as the centre of the world's Islamic economy through several things, namely strengthening the Halal value chain ecosystem and the digital ecosystem. This research uses descriptive qualitative methods, literature review type, with data collection methods through secondary data obtained from various scientific works such as journals and articles, as well as books and the internet. The research results show that the government has made many efforts to strengthen the Halal value chain and digital ecosystem by implementing appropriate policies and regulations, increasing human resources through training and mentoring, improving facilities and infrastructure, and marketing and campaigns related to halal food and halal tourism. And halal industry. These efforts have placed Indonesia in third place in the world in 2023 in the SGIE (State of the Global Islamic Economy). Keywords: SGIE, Halal value chain ecosystem, Halal food, Halal Tourism Economic creativity.